Streamlining Education Institution Through Waqf Enlargement: An Experience of Gontor System - Imam Bahroni (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2012)
Education is a process through which a person could actualize himself to be powerful individual and part of community. Powerful because he could not only live in the society but develop the community, he is also ready to lead and ready to be led and make the people dynamic. A person in this instance, who wishes to actualize his potencies, needs various trainings, positive and right movements for physics, mind and heart. First, when the physical movement continuously carried out in this life, he becomes physically strong and healthy. That is why a person needs sport, good food, and enough resting. Second, the mind also needs to be trained through various movements in the form of hard thinking on a positive and qualitative thing where the strong knowledge lays. Third, in order to strengthen his heart a person needs spiritual movement. This movement is naturally done through worship, pray and remembrance of Allah, fasting and night prayer. When these three kinds of movements practiced in life it becomes strength for the human being as an individual and part of the group of people in the society.